2010
DOI: 10.1111/j.1365-3156.2010.02609.x
|View full text |Cite
|
Sign up to set email alerts
|

Operational evaluation of a service for prevention of mother-to-child transmission of HIV in rural Uganda: barriers to uptake of single-dose nevirapine and the role of birth reporting

Abstract: Summaryobjectives To determine factors associated with pregnant women being HIV positive, barriers to the uptake of single-dose nevirapine (sdNVP) for prevention of mother-to-child transmission (PMTCT) and feasibility and effectiveness of reporting HIV-exposed infants born in facilities with no PMTCT services so as to receive NVP.methods From 2002 to 2007, a sdNVP PMTCT service was implemented in 53 rural villages of southwest Uganda. Twenty-five of them were HIV-surveillance study villages. The proportions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 9 publications
2
37
1
Order By: Relevance
“…Our results differ substantially from those of other studies in which lower adherence rates were reported from Africa 2,3 (62-73.1% adherence to a single dose of nevirapine at birth) and the U.S. (71% adherence to zidovudine in the week prior to interview) 4 using similar self-report methods. It is unclear why higher adherence was observed in our population, although a higher susceptibility to social desirability bias is a possibility.…”
Section: Dear Editorcontrasting
confidence: 99%
“…Our results differ substantially from those of other studies in which lower adherence rates were reported from Africa 2,3 (62-73.1% adherence to a single dose of nevirapine at birth) and the U.S. (71% adherence to zidovudine in the week prior to interview) 4 using similar self-report methods. It is unclear why higher adherence was observed in our population, although a higher susceptibility to social desirability bias is a possibility.…”
Section: Dear Editorcontrasting
confidence: 99%
“…The results from the two testing strategies were clearly different (p <0·001 from meta-regression). Predictors of successful HIV testing were reported in six publications [10, 17-21] and included cART provision at the antenatal clinic [21] and being accompanied by a male partner [20] (webppendix Table S2). …”
Section: Resultsmentioning
confidence: 99%
“…In three of the 34 studies the antiretroviral regimen was not specified. Information on predictors of sdNVP uptake was available in six studies [10, 13, 17, 19, 20, 23]. Uptake was better when the male partner was involved [20] and when women delivered at the health care facility [19] (webappendix Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…[2] Maintaining ARV adherence has been challenging for patients, and predicting who will be non-adherent and intervening in an effective way has been challenging for prevention of mother-to-child HIV transmission (PMTCT) programs. [3-8] Almost one half of postpartum patients included in a recent meta-analysis did not maintain an adherence level thought to be needed for virologic suppression (>80%). [9]…”
Section: Introductionmentioning
confidence: 99%